Exploring Specific Features of Transport Interchange Hubs (TIH) Design, Taking into Account the Climatic Conditions of the Russian Arctic - Dunichkin I. V.; Bleil de Souza C.; Bogachev K.; Pezzica C. (Springer Verlag, 2019)
This paper provides a more detailed analysis of the context of designing Transport Interchange Hubs (TIHs) in the Arctic Zone of the Russian Federation (AZRF). It uses a design framework proposed by another paper also submitted to his conference by the same authors [1] to discuss how green spaces can be integrated to TIHs in extreme climates to enhance the qualities of different types of spaces inside terminals considering implications of these in the overall assessment of building performance. It also discusses, the way pedestrian flow and movement is assessed and used in the design of TIH in the AZRF through advanced analysis techniques and how these could potentially be integrated with parametric design tools, finishing by considering the complexities involved in designing compact buildings, a necessary requirement to reduce heat losses and the impact of building footprint on the permafrost.